Pengelolaan tuberkulosis paru melalui peran pos TB di Desa Teluk Paman Kecamatan Kampar Kiri - Zahtamal Zahtamal; Tuti Restuastuti; Fifiz Chandra; Sri Melati Munir; Ridha Restila (Unri Conference Series: Community Engagement, 2019)
Tuberculosis (TB) is still a threat to the community in Teluk Paman Village, Kampar Kiri District, Kampar Regency. In addition, it is not yet optimal for community empowerment by the government and health workers. This is indicated by the absence of a "Pos TB Desa" and TB cadres who can assist community-based TB management in the village. The strategy of empowering the community can be done in various ways, including advocacy, community development and community movements. The purpose of this community service was to examine the implementation of community empowerment in TB prevention and control and to see the effectiveness of advocacy and training in realizing empowered cadres. The empowerment method was advocacy, forming a "Pos TB Desa" and village TB control network, training with question and answer lecture methods combined with simulations and using various educational media. This activity has provided many benefits. The community has been able to utilize the TB Village Post that is already available. This activity helps the Health Office and local government in preventing and controlling TB cases. This activity also increases the knowledge and skills of village TB Post cadres to help prevent and control TB.